Analyzing the Concept of Tawakal in Al-Palimbani’s Paradigm of Tasawuf - Pirhat Abbas (UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to see how al-Palimbani's thoughts about tawakal were studied through his famous work on Sufism, the book Sair as-Salikin ila `Ibadah Rabb al-'Alamin. Tawakal is one part of maqāmat, which is a level that must be taken by a Sufi to get to the presence of Allah, which means: surrender, entrust and represent. On the other hand, there are those who say tawakal is very closely related to monotheism because it is an element that is within a believer's Muslim, faith has faith, that belief is the foundation of faith in a Muslim who believes. Tawakal means getting rid of dependency, eliminate persuasion related to someone’s character, and guided by truths in the following character. Al-Palimbani was one of the Palembang-born archipelago Sufis who were closer to al-Ghazali. In some cases, there were many differences. Al-Palimbani Sufi teachings have a considerable influence, not only in the archipelago but also to the Middle East region. Until now al-Palimbani's work on Sufism is still widely used by Sufism or tarekat recitation groups, both in Indonesia and in other Southeast Asian 2l countries, such as in Malaysia, Brunei Darussalam, Singapore, including Thailand. Al-Palimbani offered the concept of tawakal as an absolute surrendering to Allah.